RED-LSTM: Real time emotion detection using LSTM - Labiba, Mansura Rahman; Jahura, Fatema Tuj; Alam, Sadia; Binte Morshed, Tasfia; Rahman, Wasey (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.